Ensuring the Safety of Outdoor Workers in the UAE's Summer Heat: A Responsibility Under Islamic Feqh and UAE Law (Journal of Advanced Research in Social Sciences, 2024)
This study aims to highlight and address the critical issue of protecting outdoor workers in the UAE's extreme summer heat. It emphasizes the legal and ethical obligations under Islamic principles and UAE law to ensure their safety and well-being. This study employs a mixed-methods research design, combining qualitative and quantitative approaches. Participants include outdoor workers from various sectors, such as construction, delivery services, and landscaping in the UAE. Data was collected through surveys to assess workers' awareness of their rights and safety regulations, interviews with workers and employers to understand the implementation of safety measures, and analysis of legal documents and Islamic texts to explore the ethical and legal obligations towards worker safety. This comprehensive approach provides a well-rounded understanding of the challenges and potential solutions for safeguarding outdoor workers in extreme heat. The study revealed that many outdoor workers in the UAE are unaware of their rights and safety regulations, leading to exposure to hazardous conditions. The findings emphasize the urgent need for enhanced regulatory enforcement, improved cooling infrastructure, and comprehensive education and awareness programs to protect workers' health and safety during the intense summer heat. The study underscores the necessity for robust enhanced regulatory enforcement, and innovative solutions to ensure the safety of outdoor workers. Aligning with Islamic principles and UAE laws promotes ethical practices and highlights the importance of safeguarding vulnerable workers from extreme heat conditions.